The potentiality of using chitosan and its enzymatic depolymerized derivative chito-oligosaccharides as immunomodulators - Farida H. Mohamed, Ashgan F. El-sissi, Shaymaa A. Ismail, Siham A. Ismail, Amal M. Hashem (Journal of Applied Pharmaceutical Science, 2018)
Among the various methods used for the hydrolysis of chitosan, enzymatic hydrolysis was the most preferred method. Hence, in this research, the hydrolysis of chitosan to chito-oligosaccharides was performed using partially purified Dothideomycetes sp. chitosanase with a specific activity 16.7 IU/mg protein in a reaction mixture contained enzyme/ substrate ratio 0.2 IU/mg incubated for 1 hour at 45οC. The in vivo immunomodulatory effects of both chitosan and COS in low and high doses (10 and 20 mg/kg body weight) were studied using normal mice and lipopolysaccharide (LPS)-treated mice. In the case of their intraperitoneal injection in normal mice, they caused an increase in peritoneum cell infiltration, phagocytic activity of the peritoneal macrophage, and serum level of tumor necrotic factor-α, nitric oxide, lysozyme activity, and interleukin-6. Moreover, they significantly overcome LPS-induced severe activation of all the tested parameters. The results demonstrated that both had dual activities, immune-stimulatory activity and anti-inflammatory activity. Collectively, the present study suggests that chitosan and COS can be used as endotoxin scavenger and therapeutic agents in disorders where inflammation is one of the pathological features.
Keywords: Chitosan, chitooligosaccharide,immunomodulatory.